PENGEMBANGAN MEDIA PEMBELJARAN INFOGRAFIS INTERAKTIF BERBASIS SNAPPA PADA MATA PELAJARAN SEJARAH KELAS X SMA NEGERI 4 PAGARALAM - Yunisa Martalia; Muhammad Reza Pahlevi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop an interactive infographic learning media based on the Snappa application for the Introduction to Historical Science material for tenth-grade students at SMA Negeri 4 Pagar Alam. The issue addressed is the students' need for more engaging and effective learning media to understand history material. The research method uses the ADDIE development model consisting of five stages: analysis, design, development, implementation, and evaluation. In the analysis stage, curriculum, material, and student needs analyses were conducted through interviews and Google Forms. The design stage produced an interactive infographic design with an ordered material structure supported by a storyboard. The development stage involved creating the learning media and product validation by material, language, and media experts, with validation results indicating that the media is highly feasible to use (average score 4.42). Implementation was conducted through individual trials, small group trials, and field tests, producing very positive responses with an effectiveness score of 4.65. The effectiveness evaluation using pre-tests and post-tests showed a significant increase in student learning outcomes with an N-gain value of 0.77, categorized as high. This interactive infographic media has proven valid and effective in improving history learning outcomes and student interest. The study recommends using this media as a learning tool in classrooms to enhance understanding of history material.